New Challenges in Making Plans: Putting Design back into the Applied Science of Planning. (2015) - Jones, David
Abstract: The origins of the 'planning' lie in the regional sciences and attempts to undertake social engineering of land use occupancy. Over the last 100 years planning, as a discipline, has variously dabbled in design on the margins with urban design and neo-urbanism, but has stayed staunchly in the applied science and social science realms. This penchant detrimentally affects its graduates abilities to holistically appreciate and envision the consequences of their decisions-making and plan-making, to convey strength of conviction and expertise to the community, but also to establish a solid basis upon which its professional practice applications and decision-making paradigms successfully articulate equity and comprehensiveness of rational land use and development planning and decision-making. While planning re-learnt how to legitimately evaluate design and aesthetics into planning in the 1960s through the emergent McHargian ecological design paradigm, quickly embracing it as a consequence of major environmental land use disasters that occurred 'on its watch' that were demonstrable failures of its claimed insight and professional responsibilities, it has struggled as a discipline to embrace design as an integral technology in its daily operations and expressed 'territory' of professional responsibility. This paper reviews this legacy and then charts some emergent patterns in the teaching and practice of planning in Australia that are attempting to re-position design as a legitimate and integral part of the knowledge and skills of a professional planners.